Dekadensi Moral sebagai Dampak Melemahnya Iman: Kajian Reflektif terhadap Pergulatan antara Keinginan dan Spiritualitas: Moral Decadence as a Impact of Weakening Faith: A Reflective Study of the Struggle between Desire and Spirituality - Dini Nurul Anisa (DIRASAH: Jurnal Kajian Islam, 2025)
In a modern life filled with temptations of materialism and hedonism, individuals are constantly faced with choices between fulfilling worldly desires or upholding the integrity of faith. When desire becomes the central orientation of life and exceeds the boundaries set by religious values, faith is gradually displaced, leading to the deterioration of moral character. This article aims to reflect on the phenomenon of moral decay as a consequence of weakened spiritual control over the impulses of human desire. Through a conceptual and reflective approach, this paper highlights the essential role of faith as a balancing force in confronting unchecked desires. Faith, when deeply rooted and accompanied by a strong awareness of moral responsibility, serves as a solid foundation for guiding human behavior in accordance with Islamic ethics. The decline in moral values seen in society today is not solely due to external influences, but also stems from an inner crisis that neglects the role of faith as the primary guide. Therefore, the restoration of moral character cannot be separated from the reinforcement of faith and the continuous cultivation of spiritual consciousness.